1990
DOI: 10.1207/s15326888chc1901_5
|View full text |Cite
|
Sign up to set email alerts
|

Parents' and Health Professionals' Perceptions Concerning Parental Stress during a Child's Hospitalization

Abstract: This study compared mothers', fathers', nurses', and physicians' perceptions of parents' reactions to stressful stimuli when their children were hospitalized. Thirty-six mothers, 14 fathers, 27 nurses, and 23 physicians rated 36 stressful stimuli on an inventory the investigators developed. Analysis of Variance and subsequent multiple comparison tests disclosed numerous differences between parents and health care professionals and between mothers and fathers on the Parental Uncertainty, Annoyance, Child Discom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 3 publications
1
13
0
Order By: Relevance
“…There are numerous studies from developed countries, which have emphasized the role of addressing parental stress and concerns in PICU in addition to routine care of patients. [4][5][6][11][12][13][14][15][16][17][18][19] In a study on parental stressors from Ludhiana, India, Pooni et al, 8 found that there is significant stress among parents of children admitted in PICU, where the average parental stress score was 3. In the present study, the average parental stress score was 3.5, which points out there is significant stress.…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous studies from developed countries, which have emphasized the role of addressing parental stress and concerns in PICU in addition to routine care of patients. [4][5][6][11][12][13][14][15][16][17][18][19] In a study on parental stressors from Ludhiana, India, Pooni et al, 8 found that there is significant stress among parents of children admitted in PICU, where the average parental stress score was 3. In the present study, the average parental stress score was 3.5, which points out there is significant stress.…”
Section: Discussionmentioning
confidence: 99%
“…41 However, other authors have found that mothers and fathers seem to experience the same level of stress elicited by different stimuli. 42 Other researchers have found no significant difference in stress levels between mothers and fathers. 35,39,43 In general, there were disproportionately small numbers of participating fathers in the study samples.…”
Section: Stressors Identified In Families Of Critically Ill Childrenmentioning
confidence: 93%
“…35,39,43 In general, there were disproportionately small numbers of participating fathers in the study samples. 42,43 Two studies concluded that parents' and PICU nurses' perspectives on parental stressors have significant discrepancies. Parents reported feeling more stressed by their child's behavioral and emotional response, but nurses expressed greater concern about staff communication.…”
Section: Stressors Identified In Families Of Critically Ill Childrenmentioning
confidence: 99%
See 2 more Smart Citations